Psychoemotional risk factors for non-communicable diseases in outpatient practice. Guidelines for internists - O. M. Drapkina; V. M. Shishkova; M. B. Kotova (Кардиоваскулярная терапия и профилактика, 2022)
Methodological guidelines "Psychoemotional risk factors in outpatient practice" were developed as a practical document for primary care physicians in order to expand and improve knowledge, as well as provide care to the adult population within the studied theme. The methodological guidelines include an information and content part for medical specialists and a practical part for patients, presented in the format of memos. The guidelines include the main sections: definition, structure and epidemiology of psychoemotional risk factors, psychoemotional risk factors in the clinics of internal diseases, screening of psychoemotional risk factors, prevention and correction of psychoemotional risk factors for noncommunicable diseases, non-drug care for patients, pharmacotherapy of psychoemotional disorders. The guidelines are intended for primary care physicians, for specialists who develop and implement educational programs for patients, as well as for therapeutic residents.